1981
DOI: 10.1246/bcsj.54.3556
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermolecular Hydrogen-bonding on the Luminescence Properties of Acetophenone, Characterization of Emission States

Abstract: The effects of intermolecular hydrogen-bond formation by protic solvents on the absorption and luminescence properties of acetophenone have been investigated. It has been concluded from analysis of the T←S0 absorption, phosphorescence excitation spectra and the emission characteristics that the lowest triplet state of acetophenone in its vapor phase and in nonpolar as well as in moderately polar solvents (e.g., ethanol, EPA etc.) is of n-π* character. In rigid polar media, acetophenone exhibits a very weak 1π-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
4
9
0
1
Order By: Relevance
“…This wavenumber most probably corresponds to the n C O mode in the excited S 0 (np*) state. Similar progression is found in the phosphorescence excitation spectra [49]. The appearance of the v = -progression indicates that the molecule is distorted in the relevant excited electronic state (designated as S 0 ) along this mode.…”
Section: Electronic Absorption Spectrasupporting
confidence: 70%
See 2 more Smart Citations
“…This wavenumber most probably corresponds to the n C O mode in the excited S 0 (np*) state. Similar progression is found in the phosphorescence excitation spectra [49]. The appearance of the v = -progression indicates that the molecule is distorted in the relevant excited electronic state (designated as S 0 ) along this mode.…”
Section: Electronic Absorption Spectrasupporting
confidence: 70%
“…In acetophenone molecule also, the G ! S 0 (np*) band was found to have a vibrational structure and the 0-0 band was assigned at 27692 cm À1 (361.1 nm) in 3-methyl pentane solution [49]. Unfortunately we could not measure REP (see below) of this mode owing to its weak intensity in the Raman spectra of the molecule in different solutions.…”
Section: Electronic Absorption Spectramentioning
confidence: 97%
See 1 more Smart Citation
“…TD‐DFT calculations on the optimized S 0 of 1 located its first and second triplet excited states (T 1K and T 2K of 1 ) at 83 and 84 kcal mol −1 above S 0 of 1 . These values are considerably higher than the reported energy of the triplet ketone of acetophenone (74 kcal mol −1 ) , but more similar to the energies of the triplet ketones of aliphatic ketones such as acetone (79 kcal mol −1 ) , as the C=O chromophore is not conjugated to the phenyl ring.…”
Section: Resultsmentioning
confidence: 49%
“…It is well known that radiative and non-radiative characteristics of the lowest emitting singlet and triplet states of aromatic hydrocarbons are markedly modified when N-hetero atom is introduced in the phenyl ring [1][2][3][4][5]. It is also observed that the photophysical properties of aromatic carbonyls are largely governed by the low lying singlet and triplet np * and pp * states and intra-molecular vibronic interactions among them.…”
Section: Introductionmentioning
confidence: 99%